2022
DOI: 10.1002/brb3.2557
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of math anxiety and its remediation through a digital training program in mathematics for first and second graders

Abstract: Introduction Math anxiety severely impacts individuals’ learning and future success. However, limited is understood about the profile in East Asian cultures where students genuinely show high‐level math anxiety, despite that they outperform their Western counterparts. Here, we investigate the relation between math anxiety and math achievement in children as young as first and second graders in Taiwan. Further, we evaluate whether intensive exposure to digital game‐based learning in mathematics could ameliorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 72 publications
1
14
0
6
Order By: Relevance
“…This finding is consistent with the study conducted by Ng and their colleagues (2022) which resulted in a reduction of maths anxiety levels of primary students in Taiwan after six weeks of intensive digital training (Ng et al, 2022). The study suggested that it was the sustained exposure to maths that helped reduce the negative emotions of the students towards maths, as it eliminates the expectation of an association between the source of anxiety and aversive outcomes (Ng et al, 2022).…”
Section: Sustained Exposure-based Interventionssupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is consistent with the study conducted by Ng and their colleagues (2022) which resulted in a reduction of maths anxiety levels of primary students in Taiwan after six weeks of intensive digital training (Ng et al, 2022). The study suggested that it was the sustained exposure to maths that helped reduce the negative emotions of the students towards maths, as it eliminates the expectation of an association between the source of anxiety and aversive outcomes (Ng et al, 2022).…”
Section: Sustained Exposure-based Interventionssupporting
confidence: 89%
“…Mixedmethods (61.5%) "I can maths! ": Reducing maths anxiety and increasing maths selfefficacy using a mindfulness and growth mindset-based intervention in first-year students (Samuel & Warner, 2021) The impact of mindfulness-based cognitive therapy on maths anxiety in adolescents (LaGue et al, 2019) Neural evidence for cognitive reappraisal as a strategy to alleviate the effects of maths anxiety (Pizzie et al, 2020) The impact of mindfulnessbased cognitive therapy on maths anxiety in adolescents (LaGue et al, 2019) Evaluation of maths anxiety and its remediation through a digital training program in maths for first and second graders (Ng et al, 2022) Co-development of maths anxiety, maths self-concept, and maths value in adolescence: The roles of parents and maths teachers (Wang et al, 2021) Anxiety is not enough to drive me away: A latent profile analysis on maths anxiety and maths motivation (Wang et al, 2018) The mediating role of attention in the association between maths anxiety and maths performance: An eye-tracking study (Li et al, 2022) Neural evidence for cognitive reappraisal as a strategy to alleviate the effects of maths anxiety (Pizzie et al, 2020)…”
Section: Addressing Affective Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be triggered even when solving simple arithmetic problems, especially during timed conditions (Caviola et al, 2017) and when tasks increase in complexity (Ashcraft & Krause, 2007). Negative correlations between math anxiety and math achievement have also been reported in a wide range of students (Hembree, 1990;Ng et al, 2022). Even though females generally perform equivalently well with males in mathematical achievement, females are reported to show higher self-report math anxiety (Devine et al, 2012;Else-Quest et al, 2010;Ferguson et al, 2015;Hembree, 1990;Lau et al, 2022;Maloney et al, 2012) that can likely be attributed to social-cultural or emotional factors (Beilock et al, 2007;Bieg et al, 2015).…”
Section: Problem Size Effect In Frontoparietal Circuits Is More Salie...mentioning
confidence: 99%
“…Over the last few decades math anxiety has become an interesting topic of research. There are many studies that discuss math anxiety in students such as Ng, Chen, Wu, & Chang (2022); Pantoja, Schaeffer, Rozek, Beilock, & Levine, (2020); Ramda, Gunur, Mulu, & Makur, (2021). But math anxiety can occur to anyone including teachers that requires attention too.…”
Section: Introductionmentioning
confidence: 99%